Igazak érintése a szent, a tiszta és a tisztátalan fogalma Magyarországon a cádikok iránti tisztelet megnyilvánulásaiban - Fényes Balázs (Szegedi vallási néprajzi könyvtár, 2009)
In the everyday practice of religious life, Judaism accentuates upon activity. Perception appearing in the honouring of Tzaddikim is an excellent example of how models can be proposed and can be followed in the execution of religious commandments. However, it is impossible to understand touching and the role of the Tzaddik, disregarding other forms of perception. In certain rites, the adepts not only touch the Tzaddik, they even taste the food blessed by the latter. Kissing the TzadiWs hand is firmly interwoven with the seeing of his face, the guidance, reinforcement of faith and reassurance given by his gestures and words. The experimentation of the holy during the contact with the Tzadik, reinterprets categories like clean and unclean, touchable and untouchable. The Tzadik1s perception signifies mediation in the contact with the Eternal, helps to experience the nonmaterial world and, at the same time, it represents the norms, values and models of behaviour of a given community.